Analysis and prospects of the development of the industrial Internet in the petrochemical industry - Siqi SUN (物联网学报)
In recent years, many countries have vigorously developed the transformation and upgrading of the manufacturing industry.China has promulgated a number of policies to encourage the development of the industrial Internet in various industries and regions, and it has begun to take shape.Based on the current development needs of the petrochemical industry, and the overall transformation and upgrading challenges, the problems faced by the upstream, midstream and downstream were analyzed, including upstream reliance on imports, inadequate midstream refining and chemical core technology and system capabilities, and downstream product structure layout.Several suggestions based on the development of the industrial Internet were put forward, including underlying data analysis, core technology integration, industry ecological environment, and security protection system.Finally, the prospects and research directions for the future development of the industrial Internet in the petrochemical industry were put forward.